2020
DOI: 10.1038/s41598-020-78508-7
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell characteristics promote aggressiveness of diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) may present initially in bone marrow, liver and spleen without any lymphadenopathy (referred to as BLS-type DLBCL), which is aggressive and frequently associated with hemophagocytic syndrome. Its tumorigenesis and molecular mechanisms warrant clarification. By gene microarray profiling with bioinformatics analysis, we found higher expression of the stem cell markers HOXA9 and NANOG, as well as BMP8B, CCR6 and S100A8 in BLS-type than conventional DLBCL. We further validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 69 publications
(92 reference statements)
1
2
0
Order By: Relevance
“…Next, we studied the transformative impact of PARK2 using the clonogenic assay (colony formation assay). It is a widely used experimental approach to assess the transformed characteristics of cells in vitro (11,(22)(23)(24). In agreement with our proliferative and oncogenic studies, decreased PARK2 expression enhanced colony formation in GM-B cells (Fig.…”
Section: Downregulation Of Park2 Activates Eif4b-sensitive Gene Expre...supporting
confidence: 88%
“…Next, we studied the transformative impact of PARK2 using the clonogenic assay (colony formation assay). It is a widely used experimental approach to assess the transformed characteristics of cells in vitro (11,(22)(23)(24). In agreement with our proliferative and oncogenic studies, decreased PARK2 expression enhanced colony formation in GM-B cells (Fig.…”
Section: Downregulation Of Park2 Activates Eif4b-sensitive Gene Expre...supporting
confidence: 88%
“…Bone marrow biopsy usually reveals hemophagocytosis and an interstitial distribution of large lymphoma cells with a mature B-cell phenotype. In another study by gene microarray profiling with bioinformatics analysis, higher expression of the stem cell markers HOXA9 and NANOG, as well as BMP8B, CCR6 and S100A8 were found in BLS-type than conventional DLBCL (14).…”
Section: Discussionmentioning
confidence: 95%
“…The lifespan of these patients was significantly shorter than those without overexpression of HOXA9 mRNA. The study suggested that DLBCL patients with overexpression of HOXA9 mRNA are 2.540 times more likely to have shorter overall survival period [hazard ratio = 2.540, 95%CI (1.132 to 5.697)] 22 . In addition, patients with high level of HOXA9 2.387 times are more likely having shorter progression free survival period (hazard ratio = 2.387, 95%CI = [0.876, 6.545]) 23 …”
Section: Discussionmentioning
confidence: 99%